2008
DOI: 10.1007/s11998-007-9062-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of UV crosslinkable waterborne siloxane–polyurethane dispersion PDMS-PEDA-PU and the properties of the films

Abstract: A UV crosslinkable waterborne siloxanepolyurethane dispersion, PDMS-PEDA-PU, was synthesized by incorporating acrylate groups into the side chain of the polyurethane using pentaerythritol diacrylate (PEDA). Polysiloxane groups were introduced into the soft segment of the polyurethane using polydimethylsiloxane (PDMS). They formed a crosslinking structure after UV radiation. The structure of PDMS-PEDA-PU was confirmed by the use of Fourier transform infrared spectroscopy (FTIR). X-ray diffraction (XRD) analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 13 publications
4
27
0
Order By: Relevance
“…Due to the strong hydrophobic Si-O-Si bonds and the low surface energy of HPMS-APE segments, polyurethanes had a highly hydrophobic nature, and it brought polyurethanes good hydrolytic stability and fast water release on drying 27 . Further, the water resistance of these materials was superior to that of previously published PDMS-based polyurethanes 21,22 . Accordingly, we confirmed that HBPUs derived from HPMS-APE presented excellent water resistance.…”
Section: Water Absorption Testingmentioning
confidence: 74%
See 1 more Smart Citation
“…Due to the strong hydrophobic Si-O-Si bonds and the low surface energy of HPMS-APE segments, polyurethanes had a highly hydrophobic nature, and it brought polyurethanes good hydrolytic stability and fast water release on drying 27 . Further, the water resistance of these materials was superior to that of previously published PDMS-based polyurethanes 21,22 . Accordingly, we confirmed that HBPUs derived from HPMS-APE presented excellent water resistance.…”
Section: Water Absorption Testingmentioning
confidence: 74%
“…Decomposition of the soft segments followed the polyester or the polyether. Generally speaking, the decomposition temperature for polyurethanes was at about 240 °C, but for hyperbranched polyurethanes, the decomposition temperature was higher than 300 °C 22,23 . From the data, it could be seen that the T on of HBPUs was about the same up to 320 °C and the T max1 of HBPUs changed very little, while the T max2 of all HBPUs with HPMS-APE segments were much higher than that of HBPU0 based on pure PPG.…”
Section: H-nmr and Ft-ir Spectroscopymentioning
confidence: 98%
“…This suggested that the UV-curing speed decreased by the increment of fluorine content, which meant that the fluorine chain had a negative effect on the UV-curing speed of the fluorinated polyurethane acrylate. Bai et al also found that the introduction of hydrophobic silica chain into the polyurethane system had a bad effect on the UV-curing kinetic [27].…”
Section: Synthesis and Characterization Of Uv-curable Waterborne Fpuamentioning
confidence: 99%
“…3,14,15 Nevertheless, the primary amino groups existing in the PU backbone would like to form partial crosslinking among PU molecular chains; this results in poor dispersion stability. 16 Thus, the utilization of secondary amino-terminated siloxane oligomers or hydroxylalkyl-terminated siloxane oligomers into the PU system could be a better choice, [17][18][19] but the excess siloxane oligomers, which are only blocked into PU system as chain extenders, results in a very weak mechanical strength and serious incompatibility, 2 whereas crosslinking trifunctional silane or silane-modified inorganic silica or clay could also be introduced into the PU system to form PU/silica or clay-hybrid composites. [20][21][22][23] Although the mechanical properties and water resistance were enhanced, stable properties were difficult to improve with trifunctional silane, silane-modified inorganic silica, or clay (>2.5%).…”
Section: Introductionmentioning
confidence: 99%